A Review on Environmental and Economic Impact of 2D Nanomaterials-Based Heat Transfer Fluids. (19th July 2022) - Shaik, Aabid Hussain; Shaik, Saboor; Goyal, Sparsh; Chandan, Mohammed Rehaan; Veza, Ibham; Buradi, Abdulrajak; Alarifi, Ibrahim M.
Abstract : 2D nanomaterials-based heat transfer fluids show excellent thermal properties due to their large specific surface area; hence, they find large-scale applications in automobile industries and cooling processes. Therefore, it is very essential to study the environmental and economic aspects of these 2D nanomaterial-based nanofluids. In this review, we have discussed the environmental impact of 2D nanomaterial-based heat transfer nanofluids under various conditions. The environmental impact analysis of these materials has shown excellent capability in reducing the energy consumption for heat transfer operations. Moreover, the possibility of nanomaterials and base fluid recovery makes it a sustainable alternative. In addition, health risk assessment on humans, cytotoxicity, and life cycle analysis have also been explored. The price-performance index has been successfully used to study the economic impact of 2D nanomaterial-based heat transfer fluids. The overall economic impact of 2D nanomaterial-based heat transfer nanofluids provides an optimistic perspective over conventional heat transfer fluids. Moreover, graphene production, market trend, and commercialization obstacles were also discussed.